2022
DOI: 10.3390/jpm12091422
|View full text |Cite
|
Sign up to set email alerts
|

IRO/Shift Test Is Comparable to the Jobe Test for Detection of Supraspinatus Lesions

Abstract: To determine how the internal rotation and shift (IRO/shift) test compares to the gold standard of clinical tests (Jobe test) for diagnosing supraspinatus lesions and to confirm these clinical results with surgical findings, 100 symptomatic patients were clinically examined between October 2018 and November 2019. All 100 patients were evaluated using both the IRO/shift test and Jobe test. A total of 48 of these patients received surgical intervention. Based on these data, sensitivity, specificity, positive pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similarly, the CMS has been reported to correlate with the isokinetic evaluation of the external rotation strength at the 6- and 12-month post-operative periods for rotator cuff repair [ 18 ]. In addition to functional surveys, clinical tests, such as the Jobe test [ 19 , 20 ] and the newly developed internal rotation and shift test (IRO/Shift test) [ 21 , 22 ] are used to determine the structural integrity and the functional properties of the supraspinatus tendon. Fieseler et al [ 21 ] originally reported that the IRO/Shift test is a reliable and valid tool for assessing supraspinatus tears, demonstrating both strong intra-rater and inter-rate reliability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the CMS has been reported to correlate with the isokinetic evaluation of the external rotation strength at the 6- and 12-month post-operative periods for rotator cuff repair [ 18 ]. In addition to functional surveys, clinical tests, such as the Jobe test [ 19 , 20 ] and the newly developed internal rotation and shift test (IRO/Shift test) [ 21 , 22 ] are used to determine the structural integrity and the functional properties of the supraspinatus tendon. Fieseler et al [ 21 ] originally reported that the IRO/Shift test is a reliable and valid tool for assessing supraspinatus tears, demonstrating both strong intra-rater and inter-rate reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Fieseler et al [ 21 ] originally reported that the IRO/Shift test is a reliable and valid tool for assessing supraspinatus tears, demonstrating both strong intra-rater and inter-rate reliability. These authors then performed a subsequent study comparing the IRO/Shift test to the Jobe test and found that these clinical tools are comparable in the detection of supraspinatus lesions [ 22 ]. More specifically, the IRO/Shift test had a sensitivity of 96%, a specificity of 50%, and an accuracy of 77% compared to the Jobe test, which had a sensitivity of 89%, a specificity of 60%, and a similar accuracy of 77%.…”
Section: Introductionmentioning
confidence: 99%